META-ANALISIS PENGGUNAAN EDMODO TERHADAP MOTIVASI, KEMANDIRIAN, DAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Noveridha Utama; Zulyusri Zulyusri; Rahmawati Darussyamsu (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2021)
Information technology-based learning is currently very much required by educators in the learning process, this is due to the Covid-19 pandemic condition which forces the learning process to be carried out through distance education or commonly called online. The online learning process is quite difficult for educators to monitor students’ motivation, independence and critical thinking skills. One of the efforts to carry out the online learning process is to use e-learning media by edmodo platform. Edmodo is a social network-based learning platform that can help educators and students in the virtual learning process by prioritizing the privacy of students. This study aims to analyze the use of e-learning media by edmodo platform and its relation to students’ motivation, independence and critical thinking skills. This study used meta-analysis method. The population was 21 articles that examine the application of edmodo in learning while the sample was 16 articles taken by purposive sampling technique. Data analysis used the effect size calculation technique by Glass. The result showed that the edmodo platform application in learning had an effect on increasing students’ motivation, independence and critical thinking skills. The effect of edmodo platform application is higher on students’ critical thinking skills with an effect size value of 0,43 (medium effect), followed by students’ motivation of 0,24 (small effect) and students’ independence of 0,11(negligible effect).